Dendritic Cell Derived Cytokines in Human Natural Killer Cell Differentiation and Activation - Chijioke, Obinna; Muenz, Christian (Frontiers in Immunology, 2013)
Dendritic cells (DCs) and natural killer (NK) cells shape each other’s functions early during immune responses. DCs activate NK cells and NK cells can mature or kill DCs. In this review we will discuss which DC and NK cell subsets are mainly affected by this interaction, where these encounters might take place and which signals are exchanged. Finally, we will point out what the clinical benefit of understanding this interaction might be and how it changed our view on NK cells as innate lymphocytes.